Social support and its associated factors among older adult patients with intestinal stomas: a cross-sectional study in Guangxi, China - Wei, Lijiao; Wei, Ruili; Huang, Fang; Shen, Junwen; Li, Hongjun; Li, Chanchan (Frontiers in Public Health, 2025)
BackgroundSocial support plays a crucial role in the rehabilitation and psychosocial well-being of older adult individuals following intestinal stoma surgery. However, regional disparities and influencing factors of social support in this population remain insufficiently studied, particularly in underserved areas of China. This study aimed to assess the current level of social support and identify its influencing factors among older adult patients with intestinal stomas in the Guangxi region of China.MethodsA cross-sectional study was conducted from September to December 2024 involving 162 older adult patients (aged ≥60) who underwent intestinal stoma surgery within the previous year. Participants were recruited from stoma outpatient clinics in three tertiary hospitals in Guangxi. Data were collected using a self-designed demographic questionnaire and the validated Social Support Rating Scale (SSRS). Descriptive statistics, t-tests, ANOVA, and multiple linear regression analyses were performed using SPSS 26.0 to identify significant predictors of social support.ResultsThe overall mean SSRS score was 39.12 ± 4.57, indicating a moderate level of social support. Objective support (19.81 ± 2.54) scored the highest among the three dimensions, followed by subjective support (11.45 ± 1.99) and utilization of support (7.86 ± 1.39). Multivariate analysis identified the type of primary caregiver and the presence of peristomal skin complications as independent predictors of social support (p < 0.05). Other significantly associated factors included age, education level, and the patients’ and their families’ acceptance of the stoma.ConclusionOlder adult patients with intestinal stomas in Guangxi experience moderate social support, influenced by both clinical and psychosocial factors. Targeted interventions that improve caregiver engagement and manage stoma-related complications are essential for strengthening social support systems and enhancing post-surgical outcomes in this vulnerable population.